CHARACTERIZATION AND MONOMER REACTIVITY RATIOS OF GRAFTED CELLULOSE WITH N-(4-NITROPHENYL)ACRYLAMIDE AND METHYL METHACRYLATE BY ATOM TRANSFER RADICAL POLYMERIZATION - Cankaya, Nevin; Temuz, M. Mursit (Editura Acad Romane, 2012)
N-(4-nitrophenyl)acrylamide (4NPA) original monomer was synthesized and characterized by FT-IR, H-1 and C-13 NMR techniques. The atom transfer radical polymerization (ATRP) of 4NPA with methyl methacrylate (MMA) were performed in dimethylformamide (DMF) at 130 degrees C in the presence of cellulose chloroacetate (Cell.ClAc) macro initiator, Cu(I)Cl/2,2'-bipyridine catalytic system. The graft copolymers were characterized by elemental analysis, FTIR spectra and thermal analysis. Thermal stabilities of the graft copolymers were determined by the TGA method and it was established that thermal stability of the copolymers increased with the increase of MMA units, while it decreased with the increase of 4NPA units. In order to investigate the effect of 4NPA with MMA monomer interactions on grafting, the graft copolymerization was also studied using different feed compositions, ranging from 0.15 to 0.85. The reactivity ratios of 4NPA and MMA by ATRP on cellulose were determined using the Finemann-Ross (F-R), inverted Finemann-Ross (inverted F-R), Yezrielev-Brokhina-Roskin (Y-B-R), Kelen-Tudos (K-T) and extended Kelen-Tudos (extended K-T) linearization methods. The reactive ratios of r(1) and r(2) were found to be 0.017-0.116 and 1.209-1.472, respectively. The graft copolymers on cellulose r(1).r(2) are close to zero.
Keywords: ATRP; cellulose; graft copolymer; monomer reactivity ratios